2020
DOI: 10.1016/j.lfs.2020.118230
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell degranulation and histamine release during A/H5N1 influenza infection in influenza-sensitized mice

Abstract: Here we evaluate the role of mast cells in infection with influenza A/H5N1 virus in immunized mice. CBA mice were immunized intramuscularly with formalin-inactivated A/Vietnam/1194/2004 (H5N1)NIBRG-14 (H5N1). Serum samples were obtained on days 7, 12, 14, 21 after immunization. At day 14, the mice were infected intranasally with the A/Indonesia/5/2005 (H5N1)IDCDC-RG2 (H5N1) influenza virus with half of the animals receiving a mixture of the antihistamines. 67% of the vaccinated mice were protected from the let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…We next sought to identify the sites that contributed most strongly to PC1 and found that the genes mapped to the top 200 sites were enriched in mast cell activation involved in immune responses. Our finding supports previous work that demonstrated that mast cells influence the response to influenza virus infection in mice 27 . We also mapped significant differentially methylated CpG sites post-vaccination to proximal genes and performed gene ontology enrichment analysis.…”
Section: Discussionsupporting
confidence: 93%
“…We next sought to identify the sites that contributed most strongly to PC1 and found that the genes mapped to the top 200 sites were enriched in mast cell activation involved in immune responses. Our finding supports previous work that demonstrated that mast cells influence the response to influenza virus infection in mice 27 . We also mapped significant differentially methylated CpG sites post-vaccination to proximal genes and performed gene ontology enrichment analysis.…”
Section: Discussionsupporting
confidence: 93%
“…We next sought to identify the sites that contributed most strongly to PC1 and found that the genes mapped to the top 200 sites were enriched in mast cell activation involved in immune responses. Our nding supports previous work that demonstrated that mast cells in uence the response to in uenza virus infection in mice (19). We also mapped signi cant differentially methylated CpG sites post-vaccination to proximal genes and performed gene ontology enrichment analysis.…”
Section: Discussionsupporting
confidence: 88%
“…To block the action of histamine in experiments on mice, we used a mixture of H1 and H2 blockers (although the main type of receptors on cells responsible for the anaphylactogenic effects of histamine are H1 receptors). Our previous data indicate that the introduction of histamine receptor blockers decreased in lethality after A/H5N1 infection of vaccinated mice (31). In the present study, it was shown that after challenge with the A/H1N1 virus, protection reached 90% of the immunized animals and the administration of antihistamines did not make an additional contribution to improving survival.…”
Section: Discussionsupporting
confidence: 47%